Single stage surgical excision for vascular malformation without any pre-operative adjuvant therapy: our experience regarding case selection in 20 patients - Naik, Narendra G.; Karandikar, Sangram (International Surgery Journal, 2018)
Background: Vascular malformations generally present in young population. The patients or their guardians seek treatment for alleviation of functional and/or cosmetic disfigurement. Non-invasive techniques with or without surgery are available, however surgical treatment has been found to be most definitive modality of treatment in selected cases of vascular malformations. In this article, we are presenting our experience of single stage partial/total excision of vascular malformation of various types, at different location on body without any adjuvant treatment with emphasis on the post-operative outcome. The aim of the study was to evaluate criteria for case selection, freedom from symptoms, cosmetic outcome, functional improvement, long term post-operative result and quality of life. Methods: This study was performed to assess outcome of surgical treatment for 20 patients of vascular malformation. Fourteen were offered primary surgery and 6 out of 20 had received prior non-invasive treatment. The post-operative follow-up period was minimum 6 months and maximum for 4 years. Results: The patients who underwent primary surgery were more satisfied than those who had received non-invasive treatment before surgery. This was because of satisfactory cosmetic outcome, minimal post-operative pain of short duration, no post-operative residual wound and minimal post-operative morbidity. Conclusions: For treatment of vascular malformations, surgery can be offered as the primary and only treatment modality in selected cases because of immediate resolution of mass, minimal complications, satisfactory functional outcome and acceptable cosmetic appearance. Also, this improved patient compliance and long term follow up.